Ag@Cu with Cu–CuO interface prepared by air cold-plasma promoting the electrocatalytic reduction of CO2 to low-carbon alcohols. (February 2022) - Xia, Yong; Zhang, Qiang; Guo, Fang; Wang, Jianlin; Li, Wei; Xu, Junqiang
Abstract: Bimetallic catalysts catalyst was potential catalyst for electrochemical reduction of CO2 (CO2 RR) to produce liquid fuel. Adjusting the adsorption energy of intermediates on bimetallic catalysts was very effective to improve the selectivity of electroreduction of CO2 to low-carbon alcohols. However, it was difficult to further increase the yield of low-carbon alcohols by adjusting the content ratio between metals alone. Here, in vacuum environment, we use low temperature plasma technology to treat Ag@Cu catalyst to form Cu–CuO interface on the catalyst surface, so that the selectivity and activity of the reaction were further enhanced. The performance of CO2 RR was effectively improved by the surface Cu–CuO interface. CO2 RR tests show that at −0.8 V vs RHE, the faraday efficiency of low-carbon alcohols of Ag@Cu-10 catalyst was the highest of 65.5%, which was 19.9% higher than that of Ag@Cu. In addition, the linear sweep voltammetry test showed that the current density of CO2 RR increased by 2 times, indicating that the surface Cu–CuO interface promoted the activation of CO2 on the surface of the catalyst and improved the intrinsic activity. This work introduces a technique of preparing surface Cu–CuO interface to adjust the adsorption energy of CO2 RR intermediates, which provides a new idea for the development of efficient CO2 RR catalysts. Highlights: Surface Cu-CuO interface was prepared to improve the electrocatalytic activity of CO2 . Ag@Cu exhibited excellent performance for CO2 RR to low-carbon alcohols with FE of 65.5% at -0.8 V (vs. RHE) and current density of 13 mA·cm -2 . The synergistic effect of Ag and CuO promoted the adsorption of intermediate species.